Photobiomodulation improves frontal lobe cognitive functions and mental health of older adults with non-amnestic mild cognitive impairment: Case studies - Cheung, Mei-Chun; Lee, Tsz-Lok; Sze, Sophia L.; Chan, Agnes S. (Frontiers in Psychology, 2023)
This study investigates the effect of transcranial photobiomodulation (tPBM) on improving the frontal lobe cognitive functions and mental health of older adults. Three older adults with mild cognitive impairment (MCI) of the non-amnestic type received 18-session tPBM stimulation for nine weeks and were assessed with neuropsychological tests of memory and executive functions and standardized questionnaires on depressive and anxiety symptoms, global cognitive functions, and daily functioning abilities before and after tPBM stimulation. At baseline, their intrusion and/or perseveration errors in a verbal memory test and a fluency test, as measures of the frontal lobe cognitive functions, were in the borderline to severely impaired range at baseline. After tPBM stimulation, the three older adults showed various levels of improvement in their frontal lobe cognitive functions. One older adult's intrusion and perseveration errors improved from the <1st–2nd percentile (moderately to severely impaired range) to the 41st–69th percentile (average range), another older adult’s intrusion errors improved from the 11th percentile to the 83rd percentile, and the third older adult’s intrusion errors improved from the 5th percentile to the 56th percentile. Moreover, improvements in their anxiety and/or depressive symptoms were also observed. One older adult’s depressive and anxiety symptoms improved from the severe range at baseline to the mild range after the intervention. The other two older adults’ depressive symptoms improved from the mild range at baseline to the normal range after the intervention. These findings provide preliminary support for the potential of tPBM to improve the frontal lobe cognitive functions and mental health of older adults with MCI. Given the small sample size of only three older adults and the absence of a placebo control group, larger randomized controlled studies are needed to confirm its potential.